The Effect of Frequency of Use and Ease of Use on Satisfaction of BRI Bank Users Among Students in the Greater Solo Area - Estina Vitasari; Novemy Triyandari Nugroho; Putri Intan Prastiwi (Husnayain Business Review, 2026)
Progress in information technology has led banks to launch digital offerings through mobile banking platforms, such as BRImo. This research intends to examine how usage frequency and user-friendliness affect individuals’ satisfaction with the BRImo application among students residing in the Greater Solo region. A quantitative methodology was adopted for this study, utilizing a survey technique. The target population included 50,996 students from Universitas Veteran Bangun Nusantara (UNIVET) and Universitas Muhammadiyah Surakarta (UMS). A convenience sampling approach was applied, yielding a participant group of 100 individuals. Data was gathered using a questionnaire that featured a five-point Likert scale and was analyzed with IBM SPSS Statistics involving validity assessments, reliability evaluations, classical assumption analyses, multiple linear regression evaluations, partial tests (t-tests), and R² determination coefficient tests. Findings reveal that the frequency of use positively and significantly impacts user satisfaction regarding the BRImo application. In contrast, user-friendliness does not significantly affect user satisfaction. The determination coefficient shows that 10.7% of the changes in user satisfaction can be attributed to the factors of usage frequency and user-friendliness, while the rest is affected by other elements not included in the research framework. This study aspires to offer insights for Bank Rakyat Indonesia on enhancing the service quality of the BRImo application and to serve as a basis for future investigations into mobile banking user satisfaction. Keywords: Frequency of Use, Ease of Use, User Satisfaction, BRImo, Mobile Banking.